PoGO+ polarimetric constraint on the synchrotron jet emission of Cygnus X-1. (12th December 2018) - Chauvin, Maxime; Florén, Hans-Gustav; Jackson, Miranda; Kamae, Tuneyoshi; Kataoka, Jun; Kiss, Mózsi; Mikhalev, Victor; Mizuno, Tsunefumi; Takahashi, Hiromitsu; Uchida, Nagomi; Pearce, Mark
Abstract: We report a polarimetric constraint on the hard X-ray synchrotron jet emission from the Cygnus X-1 black hole binary system. The observational data were obtained using the PoGO+ hard X-ray polarimeter in 2016 July, when Cygnus X-1 was in the hard state. We have previously reported that emission from an extended corona with a low polarization fraction is dominating, and that the polarization angle is perpendicular to the disc surface. In the soft gamma-ray regime, a highly polarized synchrotron jet is reported with INTEGRAL observations. To constrain the polarization fraction and flux of such a jet component in the hard X-ray regime, we now extend analyses through vector calculations in the Stokes QU plane, where the dominant corona emission and the jet component are considered simultaneously. The presence of another emission component with different polarization angle could partly cancel out the net polarization. The 90 per cent upper limit of the polarization fraction for the additional synchrotron jet component is estimated as <10 per cent, <5 per cent, and <5 per cent for polarization angle perpendicular to the disc surface, parallel to the surface, and aligned with the emission reported by INTEGRAL data, respectively. From the 20–180 keV total flux of 2.6 × 10 −8 erg s −1 cm −2, the upper limit of the polarized flux is estimated as < 3 × 10 −9 erg s −1 cm −2 .